Real-time PM2·5 air pollution and social preferences: a large-scale behavioural game study using mobile apps in mainland China. (September 2019) - Hong, Ying-yi; Li, King King; Huang, Bo; Tam, Tony
Abstract: Background: Air pollution undermines people's physical health. So why wouldn't people take actions to reduce air pollution? We argue that social preferences might play a part. Specifically, we examined the links between air pollution, interpersonal trust, and preferences to buy so-called sin stocks (companies that polluted the environment). Because previous research has shown that high pollution induces a belief in immorality as a social norm (akin to "broken-window" effect), we predicted that pollution is linked to lower trusting and trustworthy behaviours, and higher likelihood to buy sin stocks. Second, we examined the moderating role of participants' subjective socioeconomic status (SSES). Specifically, previous studies have shown that low SSES induces a feeling of deprivation and higher vulnerability. Therefore, we predicted an interaction between pollution and SSES, such that low SSES participants in highly polluted environment should display the lowest levels of trusting and trustworthy behaviours, and highest likelihood to buy sin stock. Methods: We recruited 4177 participants residing in 31 provinces of mainland China during January, 2018. Participants were asked to play three incentivised behavioural games measuring their likelihood to buy sin stocks, trusting behaviour, and trustworthiness, respectively. We disseminated our survey via a mobile phone application, making it possible to pay the participants according to their performance on the games, and estimate the instantaneous, real-time air pollution (PM2·5 ) from dynamic monitoring station data based on each participant's GPS information. Findings: We found a robust main effect of pollution and an interaction effect between SSES and real-time PM2·5 levels, as we had predicted. Interpretation: Our findings counter the common wisdom that people are motivated to take actions to improve their own environment. Instead, a polluted environment could create a bad norm that undermines trust and environmental protection. Funding: Partial funding came from a seed grant for the Chinese University of Hong Kong (CUHK)—Chinese Academy of Social Sciences (CASS) Research Collaboration on Social Psychology offered by the Research Committee of CUHK.